MPLEMENTASI ALGORITMA C4.5 UNTUK MENENTUKAN ATURAN REKOMENDASI CALON PENERIMA BEASISWA - Ratna Rahmawati Rahayu (INFOKOM (Informatika & Komputer), 2019)
The database as a medium for storing and processing data has become a necessity in every agency, company and individual. Each transaction or event is stored in the database, so the database size is even greater. One of them is an academic database that stores student identity and achievement data. By utilizing the existing database, it is expected to determine the recommendations of eligible students as prospective scholarship recipients.One technique for finding useful information from large databases is the C4.5 algorithm which is a classification method of data mining. From academic databases, some fields are supported in the scholarship requirements, then processed based on the stages of data mining with C4.5 algorithm technique, and the results are in the form of a decision tree that can be used to determine student feasibility recommendations as prospective student recipients.